2010
DOI: 10.1155/2010/849169
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Health Hazards in ICU Nursing Staff

Abstract: This study analyzed occupational health hazards for Intensive Care Unit (ICU) nurses and nursing technicians, comparing differences in the number and types of hazards which occur at the beginning and end of their careers. A descriptive cross-sectional study was carried out with 26 nurses and 96 nursing technicians from a public hospital in the Federal District, Brazil. A Likert-type work-related symptom scale (WRSS) was used to evaluate the presence of physical, psychological, and social risks. Data were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 17 publications
1
10
0
8
Order By: Relevance
“…Greater prevalence or severity of symptoms may be due to the higher demands and constraints that women face or because women are more affected by, or vulnerable to, the health impact of particular demands and constraints (26). A study at a public hospital in Brazil of occupational health hazards for intensive care unit nurses and nursing technicians reported that leg pain and sleep disturbance symptoms were at critical levels among nurses; among nursing technicians, critical levels were detected for leg and back pains (27).…”
Section: Discussionmentioning
confidence: 99%
“…Greater prevalence or severity of symptoms may be due to the higher demands and constraints that women face or because women are more affected by, or vulnerable to, the health impact of particular demands and constraints (26). A study at a public hospital in Brazil of occupational health hazards for intensive care unit nurses and nursing technicians reported that leg pain and sleep disturbance symptoms were at critical levels among nurses; among nursing technicians, critical levels were detected for leg and back pains (27).…”
Section: Discussionmentioning
confidence: 99%
“…Although few population-based studies have examined the prevalence of clinically diagnosed mental health disorders among cancer patients, those have mostly been in mixed inpatient and outpatients records [ 17 , 32 ] or only outpatients [ 18 ]. To put the findings of our study into context, the prevalence found here is much higher than observed in one study of colorectal cancer outpatients [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although few population-based studies have examined the prevalence of clinically diagnosed mental health disorders among cancer patients, those have mostly been in mixed inpatient and outpatients records [ 17 , 32 ] or only outpatients [ 18 ]. To put the findings of our study into context, the prevalence found here is much higher than observed in one study of colorectal cancer outpatients [ 18 ]. Zhang and Cooper reported that the clinical diagnostic rates among colorectal cancer outpatients who were Medicare beneficiaries in 2002 was 1.5% for depressive disorders, and 1.1% for anxiety disorders, and in non-cancer outpatients approached 2.5% for depressive disorders and 1.6% for anxiety disorders [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Para o aspecto psicofisiológico, aparecem em destaque os distúrbios do sono, e dores nas costas e pernas. Quanto aos aspectos sociais, o foco repousa sobre a dificuldade de relacionamento familiar; e, sobre aspecto psicológico, a tristeza, irritação por qualquer motivo e perda da autoconfiança (SHIMIZU et al, 2010).…”
Section: Considerações Sobre O Trabalho Da Equipe De Enfermagem Emunclassified
“…Neste local, há grande relação entre a organização do trabalho e estresse, principalmente, para os trabalhadores da enfermagem , SHIMIZU et al, 2010, ALVES, 2013).…”
Section: Discussão O Trabalho Na Uti Ambiente E Estresse Laboralunclassified